2022
DOI: 10.3390/ijerph19052492
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Obesity Tendency and Nutritional Status Is Related to the Risk of Sarcopenia, Frailty, Depression and Quality of Life in Patients with Dementia

Abstract: The purpose of this study was to investigate the nutritional status of dementia patients and examine the correlation with sarcopenia, frailty, depression, and quality of life. We enrolled patients aged 60 years and over with Mini Mental State Examination (MMSE) scores ≤ 26 (Taiwan), and dementia diagnosed by a neurologist or psychiatrist. Nutritional status was assessed with the Mini Nutritional Assessment (MNA). Muscle mass was measured by dual-energy X-ray absorptiometry. Muscle strength and endurance were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…In the study, in which 36 patients were included and sarcopenic obesity was evaluated with DEXA measurements, sarcopenic obesity was observed in 5 female patients 47 . The prevalence of sarcopenic obesity was found to be 58.3%, although, unlike our study, the sarcopenic obesity prevalence in the mild and moderate dementia groups was similar 48 …”
Section: Discussioncontrasting
confidence: 72%
“…In the study, in which 36 patients were included and sarcopenic obesity was evaluated with DEXA measurements, sarcopenic obesity was observed in 5 female patients 47 . The prevalence of sarcopenic obesity was found to be 58.3%, although, unlike our study, the sarcopenic obesity prevalence in the mild and moderate dementia groups was similar 48 …”
Section: Discussioncontrasting
confidence: 72%
“…Recent data suggest that preserving muscular mass (with a larger calf circumference) and avoiding central obesity might help prevent functional impairment even in centenarians (Stern, 2002 ). Similar to sarcopenia, SO has been linked to frailty and osteoporosis (Fan et al, 2021 ; Chou et al, 2022 ). Moreover, individuals with SO are at greater risk of metabolic disorders and reduced physical performance, such as walking speed, than those with sarcopenia or obesity alone (Sun et al, 2021 ; Tan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to some previous reports, the prevalence of SO in Chinese community-dwelling older adults was estimated at 6.0–25.0% (Chang et al, 2016 ; Chen et al, 2021 ; Cheng et al, 2022 ). SO is associated with poor health outcomes including frailty, disability (Choe et al, 2018 ), fractures, falls (Chou et al, 2022 ), cancer (Daviglus et al, 2010 ), cardiometabolic diseases (Donini et al, 2020 ), chronic kidney disease (Dye et al, 2017 ), and increased mortality (Espeland et al, 2022 ). Those who suffer from this geriatric syndrome are at risk of synergistic complications that can eventually result in long-term functional decline.…”
Section: Introductionmentioning
confidence: 99%
“…Depression significantly increases the risk of cardiovascular disease in older adults, according to a recent prospective cohort study ( Yu et al, 2022 ). In addition, a study of people with dementia found that the risk of malnutrition was significantly associated with muscle function and the risk of sarcopenia, frailty, depression, as well as reduced quality of life in people with dementia ( Chou et al, 2022 ). Moreover, the results of a large cross-sectional study of malnutrition in older patients with obesity using the Comprehensive Geriatric Assessment suggested that malnutrition in patients with obesity is associated with depression ( Soysal et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%